Addendum to 'The paradoxical zero reflection at zero energy' (2017 Eur. J. Phys.38 025401). (28th May 2021) - Ahmed, Zafar; Sharma, Vibhu; Sharma, Mayank; Singhal, Ankush; Kaiwart, Rahul; Priyadarshini, Pallavi
Abstract: The probability of reflection R ( E ) off a finite attractive scattering potential at zero or low energies is ordinarily supposed to be 1. However, in Ahmed Z et al (2017 Eur. J. Phys. 38 025401) we proposed that a fully attractive potential presents a paradoxical result of R (0) = 0, when an effective parameter q of the potential admits special discrete values. In an interesting comment to Ahmed et al (2017 Eur. J. Phys. 38 025401); by 5 van Dijk and Nogami (2017 Eur. J. Phys. 38 038002), another class of finite potentials turned out to be of the well–barrier type, which can be made to possess much less reflection at zero and low energies for a band of low values of q . Such well–barrier potentials have only two real turning points for E ∈ (min ( V ( x )), max ( V ( x ))), excepting E = 0. Here, we wish to add one more exactly solvable and two numerically solved models to confirm this phenomenon in the well–barrier systems.